Influence of the Photothermal Interaction under Lord-Shulman Model on a Viscothermoelastic Semiconducting Solid Cylinder Due to Rotational Movement - Hamdy M. Youssef; Alaa A. El-Bary (Novel Perspectives of Engineering Research Vol. 3, 2021)
This study investigates the photothermal interaction of an isotropic, homogeneous, semiconducting, viscothermoelastic solid cylinder in the context of Lord and Shulman’s generalized thermoelasticity theory. The cylinder rotates with a constant angular velocity around its axis. The cylinder’s outside surface has been thermally shocked. The governing equations were built in the Laplace transform domain and numerical inversions of Laplace were computed using the Tzou technique. The numerical findings for the carrier density increment, temperature increment, strain, stress, and stress-strain energy of a photogenerated carrier have been visually depicted with various values of mechanical relaxation time, angular velocity parameter, and lifespan parameter. The mechanical relaxation time and angular velocity of the rotation parameter have little influence on the carrier density function and temperature increment, but they have a substantial effect on the strain, stress, and stress-strain energy. The lifetime parameter of the photogenerated carrier has critical consequences for all functionalities investigated.